Studi Literatur Pengaruh Keadilan Distributif dan Keadilan Prosedural Pada Konsekuensinya Dengan Teknik Meta Analisis - Heru Kurnianto Tjahjono (Faculty of Psychology, Universitas Gadjah Mada, 2008)
The purpose of this literature study is to investigate whether the two factor model was supported on any empirical studies: (1) whether distributive justice is more domi¬nant compared to procedural justice when predicting personal outcomes? (2) whether procedural justice is more dominant compa¬red to distributive justice in predicting organ¬i-zational outcomes? Meta-analysis approach were done based on 13 empirical studies from any international journals. The results show that the two factor model was supported. Keywords: Distributive justive, procedural justive, meta-analysis.